Neoliberalism and Urban Change: Stretching a Good Idea Too Far?. Issue 2 (2nd April 2016) - Le Galès, Patrick
Abstract: Does neoliberalism matter for cities, urbanization processes, urban governance and policies? How and to what extent? What does this even mean? These questions are important as neoliberalism is a contentious and powerful political project and paradigm. This paper argues that: (1) it may be fruitful to be clearer about the meaning of neoliberalism rather than adopting an encompassing constructivist framework; and (2) that neoliberalism may not explain that much about the current transformation of urbanization processes and cities. Instead, these mechanisms need to be better specified and their limits defined: urban worlds and the urbanization processes of cities do not change all the time, in all ways. Rather than embracing the multiple, ever-changing forms of neoliberalism and the contructivist framework underpinning this position, this paper identifies a set of central points to define neoliberalism by contrast to liberalism, as one possible working definition of neoliberalism. Secondly, it discusses the neoliberalization of cities and urban policies, recognizing that cities change for many reasons, of which neoliberalism is just one.